Pre-Extension Demonstration of Irish Potato (Solanum Tuberosum L.) in Midlands of Guji Zone, Oromia, Ethiopia - Basha Kebede (International Journal of Scientific Multidisciplinary Research, 2024)
Potato is an interesting root crop used for food security due to its early maturity and compatibility with double cropping for farmers in the midlands of the Guji zone. However, using verified tuber seed is challenging for potato production. Therefore, verifying improved potato variety in the form of demonstration prior to large extension is necessary on the specified agroecology. This study was conducted to increase farmers' knowledge and abilities in potato cultivation, measure productivity and profitability, and assess farmers' preferences for potato farming. Adola Rede and Arda Jila Mea Boko districts were purposefully chosen. Twelve farmers were selected and planted Gudane and Zemen varieties on a 10x10m area with 70 and 30 cm inter and intra row spacing, respectively. Training was employed to help farmers enhance their knowledge and skills. Interviews were conducted to gather information about yield, production costs, and farmer preferences. The data was analyzed using descriptive statistics, t-tests, and net benefit. The demonstration results revealed that the Gudane variety yielded 20.8 t/ha, while the Zemen variety yielded 17.09 t. There was a significant difference in mean yield between Gudane and Zemen variety production at 0.001 levels. Production of Gudane and Zemen varieties returned 117083.33 birr/ha and 87416.67 birr/ha, respectively. Farmers preferred Gudane variety due to its higher yield and tolerant to disease than Zemen variety. Thus, Gudane variety was recommended for large extension production at midland districts of Guji zone